University Lecturers’ Perception of Factors Responsible for Elections Malpractices in Nigeria - Abanobi, C. C. (Innovare Journal of Education, 2023)
This study investigated university lecturers’ perceptions of factors responsible for election malpractice in Nigeria. A research question and three null hypotheses guided the study. A survey research design was used in the study. The population for this study consisted of lecturers in public universities in Delta State. The sample of this study was 300 lecturers in three public universities in Delta State. The instrument used for data collection was a structured questionnaire titled Factors Responsible for Election Malpractice in Nigeria Questionnaire. Experts validated the instrument. Cronbach Alpha method was used to determine a reliability coefficient of .79. Mean (M) and standard deviation (SD), as well as t-test statistics, were used to answer the research question and null hypotheses, respectively. The findings revealed that disregard for the electoral act by the Independent National Electoral Commission (INEC) and vote buying among various political parties to win elections by all means, among others, are perceived factors responsible for election malpractice in Nigerian university lecturers in Delta State. The difference between perceptions of factors responsible for election malpractice in Nigeria among university lecturers is not significant based on gender, rank, and religion. Based on the findings, it was recommended, among others, that the government at various levels always uphold the rule of law, especially the electoral act, during and after elections in Nigeria. The INEC should be very transparent at different stages of the election, especially during the collation process. The judiciary should prosecute electoral offenders or politicians who engage in election malpractice to deter others in society. The government at all levels as well as various stakeholders should ensure that there is proper public voter enlightenment before elections in Nigeria.